Opening model of natural ventilation windows for East-China Multi-span Plastic Greenhouse and studies on it - SI Hui-ping; MIAO Xiang-wen (浙江大学学报. 农业与生命科学版)
Natural ventilation has taken very important role in adjusting the thermal environment of East-China Multi-span Plastic Greenhouse. Using Bernoulli equation and continuity equation of hydrokinetics, setting up the high-point temperature in greenhouse, the dynamic opening model of natural ventilation windows was set up, which has relations with the temperature out greenhouse, wind speed, time, geographic position and structure of greenhouse. Finally using this model to control the opening of ventilation windows, the temperature data measured in greenhouse had good agreement with the requirement. These results proved the model could control the temperature of East-China Multi-span Plastic Greenhouse under nature ventilation condition and did the based theoretical analysis of intelligent control for the East-China Multi-span Plastic Greenhouse.